Mirror aneurysm of ICA terminus associated with adult polycystic kidney disease - Erok, Berrin; Win, Nu Nu; Can, Orçun; Çizmeli, Muzaffer Olcay (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Bilatereal saccular cerebral aneurysms (SCAs) that developed symmetrically on the same named vessels are defined as mirror aneurysms and account for a small subset of multiple cerebral aneurysms. The internal carotid artery (ICA) bifurcation is a rare location for mirror aneurysms. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. We aimed to present the importance of risk status assessment for SCAs and screening in all ADPKD patients for timely detection and managementof SCAs before catastrophic complications occur. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. We present mirror aneurysms of bilateral ICA bifurcation that appear like a couple of dancing men on coronal computed tomography angiography (CTA) images, which were successfully treated with single stage coil embolization in a 45 year old female patient with medical history of autosomal dominant policystic kidney disease (ADPKD). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. SCAs are more frequent in patients with ADPKD than in general population and also these aneurysms are more likely to rupture at earlier ages. Mirror aneurysms of ICA terminus can be treated effectively and safely by single stage coil embolization.